2018 IEEE Wireless Communications and Networking Conference (WCNC) 2018
DOI: 10.1109/wcnc.2018.8377313
|View full text |Cite
|
Sign up to set email alerts
|

Towards autonomy: Cost-effective scheduling for long-range autonomous valet parking (LAVP)

Abstract: Continuous and effective developments in Autonomous Vehicles (AVs) are happening on daily basis. Industries nowadays, are interested in introducing less costly and highly controllable AVs to public. Current so-called AVP solutions are still limited to a very short range (e.g., even only work at the entrance of car parks). This paper proposes a parking scheduling scheme for long-range AVP (LAVP) case, by considering mobility of Autonomous Vehicles (AVs), fuel consumption and journey time. In LAVP, Car Parks (CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Autonomous Vehicle (AV) is a fundamental unit of the smart city and SPS concept. The authors in [52] suggested a scheduling scheme for Long-range Autonomous Vehicle Parking (LAVP). The scheme considers AV's fuel consumption rate and the time it is traveling.…”
Section: Smart Parking System Surveymentioning
confidence: 99%
“…Autonomous Vehicle (AV) is a fundamental unit of the smart city and SPS concept. The authors in [52] suggested a scheduling scheme for Long-range Autonomous Vehicle Parking (LAVP). The scheme considers AV's fuel consumption rate and the time it is traveling.…”
Section: Smart Parking System Surveymentioning
confidence: 99%
“…4. AVP at Low Autonomous Level [53] level 2, drivers can stay out of the vehicle to monitor and control the overall parking process through smart devices, e.g., mobile phones. The level 3 applies advanced sensing and 3D mapping technologies to avoid obstacles and find out the best route towards car park [54].…”
Section: Level 1bmentioning
confidence: 99%
“…Long-range Autonomous Valet Parking (LAVP) presents a novel approach, making an autonomous vehicle temporary park in a car park within an urban area. The authors of [17] state that the Scheduling Center is the core, as it coordinates the nearest route to a drop-off place and find the best car park. This approach will benefit users by providing a reservation system in a cost-effective manner.…”
Section: Introductionmentioning
confidence: 99%